1995
DOI: 10.1136/hrt.74.6.592
|View full text |Cite
|
Sign up to set email alerts
|

Can early closure and restenosis after endoluminal stenting be predicted from clinical, procedural, and angiographic variables at the time of intervention?

Abstract: Conclusions-Clinical, procedural and angiographic variables increase the risk for early closure and restenosis after endoluminal stenting. The prediction models described above need to be validated prospectively. (Br HeartJ7 1995;74:592-597)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
1
9
1
1
Order By: Relevance
“…These differences were not statistically significant in our study, but show similar trends to previous data which suggested that the risk of thrombosis was greatest in LAD lesions 26. The reason for this is unclear, although it could reflect more frequent deployment as a bailout procedure 27. In our patient population this was not the case; indeed the rate of stenting for bailout was 22% among LAD lesions compared with 23% in other vessels.…”
Section: Discussionsupporting
confidence: 85%
“…These differences were not statistically significant in our study, but show similar trends to previous data which suggested that the risk of thrombosis was greatest in LAD lesions 26. The reason for this is unclear, although it could reflect more frequent deployment as a bailout procedure 27. In our patient population this was not the case; indeed the rate of stenting for bailout was 22% among LAD lesions compared with 23% in other vessels.…”
Section: Discussionsupporting
confidence: 85%
“…The acute thrombosis rate in this study was 4%, lower than those previously reported [3,21,22]. This rate has in fact fallen, despite the adoption of a simpler antithrombotic regimen, from 4/64 (6%) cases, in the period up until the change, to 2/93 (2%), in the period after the change.…”
Section: Discussioncontrasting
confidence: 81%
“…In several large studies, analyses were performed assuming the independence of lesions in their risk for restenosis. [4][5][6][7] This assumption was based on results from a previous study, which found no correlation between lesions of the same patient with regard to late loss 6 months after PTCA, stenting, or atherectomy in a limited number of patients with multilesion interventions. 8 In that study, the interrelation of lesions was tested by adoption of a modified form of the general linear model, which is appropriate if the error term is normally distributed.…”
mentioning
confidence: 99%